Evolution of US foot-and-mouth disease response strategy. Issue 1 (28th January 2014) - Allen, Heather; Taylor, Alexandra
Abstract : Purpose: – The purpose of this paper is to examine the experiences of the USA and other nations with developed veterinary infrastructure and identify the critical factors that led the evolution of the US foot-and-mouth disease (FMD) response strategy. Design/methodology/approach: – A thorough literature review was conducted, including official reports of US FMD outbreaks and peer-reviewed articles on outbreaks in previously FMD-free countries. Textual analysis was conducted on past and current publicly available US FMD response plans, identifying the use of the term "vaccination" or "emergency vaccination" indicating the potential use of these strategies. Findings: – The USA has shifted from a strategy of exclusively stamping-out to a response strategy that would consider emergency vaccination, including vaccinate to slaughter and vaccinate to live, in any FMD outbreak. The factors that led to this shift in policy include economic factors, the emergence of new vaccine technologies, the changed landscape of the US livestock industry, and the experiences of other typically FMD-free countries. Originality/value: – An outbreak in the USA is likely to rapidly outpace the current capacity for stamping-out. Experience from other FMD outbreaks, and lack of publicly available literature from the USA, indicates that it is critically important that further consideration, sufficient attention, and stakeholder deliberation need to occur to ensure vaccination strategies (to live and to slaughter) are implementable in an outbreak.